1994
DOI: 10.3758/bf03205314
|View full text |Cite
|
Sign up to set email alerts
|

Local and global factors of similarity in visual search

Abstract: Effects of the similarity between target and distractors in a visual search task were investigated in several experiments. Both familiar (numerals and letters) and unfamiliar (connected figures in a 5 x 5 matrix) stimuli were used. The observer had to report on the presence or absence of a target among a variable number of homogeneous distractors as fast and as accurately as possible. It was found that physical difference had the same clear effect on processing time for familiar and for unfamiliar stimuli: pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…This suggests that the feature binding requirement of the FC task increased the attentional load of the task over and above any increase induced by greater task difficulty. Findings from the human cognitive literature support this proposition: even after controlling for target-distractor similarity, which makes both FS and FC tasks more attentionally demanding, feature binding in itself requires additional attentional resources over and above those needed for making fine perceptual discriminations (Carter, 1982;Duncan and Humphreys, 1989;von Grünau et al, 1994;Foldi et al, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…This suggests that the feature binding requirement of the FC task increased the attentional load of the task over and above any increase induced by greater task difficulty. Findings from the human cognitive literature support this proposition: even after controlling for target-distractor similarity, which makes both FS and FC tasks more attentionally demanding, feature binding in itself requires additional attentional resources over and above those needed for making fine perceptual discriminations (Carter, 1982;Duncan and Humphreys, 1989;von Grünau et al, 1994;Foldi et al, 2005).…”
Section: Discussionsupporting
confidence: 48%
“…In both search (von Grünau, Dubé, & Galera, 1994) and nonsearch (Mason, 1982;Zegarra-Moran & Geiger, 1993) conditions, the perception of letters and figures has been compared, but to our knowledge, no clear dissociation between letters and shapes, as in the present experiments, has previously been obtained (although Huckauf et al, 1999, reported larger effects of lateral masking for nonletters than for letters). According to the integration strategies hypothesis, this is because these experiments fail to require their participants to distinguish between letters and shapes.…”
Section: Discussionmentioning
confidence: 60%
“…Participants were asked to locate the target square in the stimulus array and to indicate the orientation of the line inside by key press. Target‐nontarget similarity was low when the nontargets were circles, but it was high when nontargets were diamonds, that is, squares rotated by 45° (Von Grünau, Dube, & Galera, ). In order to measure ERPs to the distractor, we used a set size of eight so that two elements could be placed on the vertical midline, above and below the fixation point (see Figure ).…”
Section: Methodsmentioning
confidence: 99%